PENERAPAN MEDIA VISUAL BERBASIS GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS II PADA MATA PELAJARAN AKIDAH AKHLAK DI MI ATTARAQIE PUTRA MALANG - Alif Dho'i Akbar; Ika Ratih Sulistiani; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
The study is aimed to know how to describe the implementation of visual media of picture series and describe the increasing of the result of students’ learning through the implementation of the visual media of picture series at students of second grade A of MI Attaraqqie Putra Malang. This study used classroom action research design. The steps of this study are planning, implementation, observation and reflrction. This siklus stopped if it has achieve the purpose of the study. The subject of this study was the students of second grade A of MI Attaraqqie Putra Malang, the students consist of 34 male students. The resultd of this study were the first, the implementation of the visual media of picture has done as well based on the steps the learning have arranged. The second is the implementation of visual media of picture can increase the result of students’ learning. Based on the conclusion, the research suggest that the teacher will be able to use visual media of picture as supporter of media at the course of Akidah Akhlak.Keywords: Image Based Media Visual, Student Learning Outcomes.